Biomass and floristic composition of Bangi Permanent Forest Reserve, a twice-logged lowland dipterocarp forest in Peninsular Malaysia - Lajuni, J.J.; Latiff, A. (Universiti Kebangsaan Malaysia, 2013)
A 1 ha permanent plot was established in Bangi Permanent Forest Reserve for this study. A total of 1018 trees with a diameter at breast height (DBH) of 5 cm and above were identified, marked and measured. Their DBH ranged from 5 to 83.6 cm, where most trees fell into the 5 to 14.9 cm DBH or Class 1 (65.71%) and 1.57% of them fell into Class 7 with DBH over 65 cm. The five largest trees were from the dipterocarp family. Species with the highest Relative Dominance Value was Shorea acuminata with a value of 10.40. The total above ground biomass was 362.13 t/ha, which can be considered high for a twice-logged forest. The total basal area was 314.97 m2. The species diversity Shannon-Wiener index for this plot is H=6.99 with evenness of 0.852 and 0.85 with Brillouin’s Index. Species with the highest frequency (68.39%) and highest Importance Value Index (83.80%) was Antidesma cuspidatum. There were 171 species of trees representing 113 genera and 43 families plot. Wild fruit trees and trees with ethnobotanical potential were also identified. The results of this study indicated that this forest has high biomass content and high species diversity.